Rebating Revenues from Unilateral Emissions Pricing - Christoph Böhringer; Carolyn Fischer; Nicholas Rivers (CESifo GmbH, 2024)
This paper evaluates alternative options for rebating revenues from a unilateral emissions price, focusing on energy-intensive and trade-exposed industries. A theoretical model is developed to demonstrate that conditional rebating policies—which would be distortionary in a first-best world—may be welfare-improving. For example, this could occur in a context where emissions leakage and terms-of-trade changes are associated with the introduction of an emissions price, or when political constraints prevent the emissions price from fully reflecting the social cost of the e missions. A numerical simulation model is used to quantify the differences in welfare, leakage, terms of trade, output, and emissions across carbon prices with alternative rebating options for these leakage-prone industries. The different situations of the European Union and the United States are used as examples. The findings indicate that from a domestic perspective, rebating emissions revenues proportionately to firm output is typically superior to other rebating options when the emissions price is set close to the social cost of emissions. Rebating emission revenues to reward reductions in emissions intensity is typically superior when emissions are significantly under-priced. A country that is more emissions-intensive and less exposed to leakage may prefer to rebate in proportion to total abatement when the emissions price is sufficiently low. The quantitative results indicate that there are significant welfare losses for incorrect choices of the rebating option.
Keywords: D58; D62; H23; Q58; 330; unilateral climate policy; carbon pricing; revenue recycling